How To Get From Where You Are To Where You Want To Be: The 25 Principles Of Success - Jack Canfield
Within minutes of reading this book you will want -- and be able -- to apply its clear, direct and highly effective principles to your own life. Jack Canfield, author of Chicken Soup for the Soul, built an $80 million business from nothing. Now he shares his key techniques and unique insights so that you too can achieve success in everything you do. If you keep on doing what you've always done, you'll keep getting what you've always got. Isn't it time you changed for the better? Jack Canfield's extraordinary insights and powerful life tools will enable you to become the happy, successful person you know you are meant to be -- without burning out. Whether you want greater success and fulfilment at work, financially, in your relationships, with your health, in sports or creativity, Canfield will show you how. / Take control of your life -- 100% responsibility, 100% fulfilment / Discover and focus on your core genius -- be better at what you do best; be a huge success at what you enjoy most / Set your goals and achieve them -- transcend other people's limiting opinions.